Pigmented basal cell carcinoma in upper eyelid: a case report - Raquel de Melo Carvalho; Thaiana Botarelli; Aline Corrêa; Juliana Corrêa Marques da Costa (Sociedade Brasileira de Dermatologia (SBD), 2020)
Basal cell carcinoma (BCC) is more common in the lower eyelid region when it affects the periorbital region. It occurs predominantly in men between 50-70 years and has a high recurrence rate. Although it rarely metastasizes, orbital invasion can occur. This study aims to present a case of pigmented BCC of unusual location. The location of BCC in the upper eyelid region is rare, and dermoscopy is essential to distinguish it from its primary differential diagnoses.